IMPLEMENTASI PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM KURIKULUM MERDEKA PADA PEMBELAJARAN PAI DI SMA ISLAM GLOBAL SURYA - Asip Ependi; Baharudin; Agus Pahrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of deep learning in Islamic Religious Education (IRE) subjects in the Merdeka Curriculum and the factors that influence it. The research problem stems from the suboptimal and uneven application of deep learning in IRE teaching practices at the secondary school level. This study uses a qualitative approach with a case study design. Data were collected through learning observations, in-depth interviews with school principals, IRE teachers, and students, as well as a study of learning tools documentation. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing, using George C. Edwards III's policy implementation theoretical framework. The results show that the implementation of deep learning in PAI learning has been adaptive and is beginning to lead to meaningful and reflective learning, but it is not yet fully systemic. The main obstacles include differences in teachers' understanding of the concept of deep learning, limited learning time, limited learning resources, and suboptimal authentic assessment. The conclusion of the study confirms that the success of deep learning implementation in PAI learning is highly determined by the effectiveness of policy communication, resource availability, implementers' disposition, and support from the school bureaucratic structure.